Effect of Pet Dogs on Children's Perceived Stress and Cortisol Stress Response. Issue 2 (28th July 2016) - Kertes, Darlene A.; Liu, Jingwen; Hall, Nathan J.; Hadad, Natalie A.; Wynne, Clive D. L.; Bhatt, Samarth S.
Abstract: The present study tested whether pet dogs have stress‐buffering effects for children during a validated laboratory‐based protocol, the Trier Social Stress Test for Children (TSST‐C). Participants were 101 children aged 7–12 years with their primary caregivers and pet dogs. Children were randomly assigned in the TSST‐C to a pet present condition or one of two comparison conditions: parent present or no support figure present. Baseline, response, and recovery indices of perceived stress and cortisol levels were computed based on children's self‐reported feelings of stress and salivary cortisol. Results indicated that in the alone (no social support) condition, children showed the expected rise for both perceived stress and cortisol response to stress. Pet dog presence significantly buffered the perceived stress response in comparison to children in the alone and parent present conditions. No main condition effect was observed for cortisol; however, for children experiencing the stressor with their pet present, lower cortisol response to stress was associated with more child‐initiated petting and less dog proximity‐seeking behavior. The results support the notion that pet dogs can provide socio‐emotional benefits for children via stress buffering.